7
$\begingroup$

I want to use the Maclaurin series of $\arctan (x)$ to show that \begin{align}\int_{0}^{\pi/ 2} \arctan (a \sin x) \, \mathrm dx &= 2 \sum_{k=0}^{\infty} \frac{\left(\frac{\sqrt{1 + a^{2}}- 1}{a}\right)^{2k+1}}{(2k+1)^{2}} \\ &= \operatorname{Li}_{2} \left(\frac{\sqrt{1+a^{2}}-1}{a} \right) - \operatorname{Li}_{2} \left(\frac{1-\sqrt{1+a^{2}}}{a} \right). \end{align}

I guess we should first impose the restriction $ |a| \le 1$.

Then we have

$$ \begin{align} \int_{0}^{\pi/ 2} \arctan (a \sin x) \ dx &= \int_{0}^{\pi /2} \sum_{k=0}^{\infty} (-1)^{k} \, \frac{(a \sin x)^{2k+1}}{2k+1} \, \mathrm dx \\ &= \sum_{k=0}^{\infty} (-1)^{k} \, \frac{a^{2k+1}}{2k+1} \int_{0}^{\pi /2} \sin^{2k+1} (x) \, \mathrm dx \\ &= \sum_{k=0}^{\infty} (-1)^{k} \frac{a^{2k+1}}{(2k+1)^{2}} \frac{2^{2k}}{\binom{2k}{k}}. \end{align}$$

But how do we proceed from here?

$\endgroup$
6
$\begingroup$

Here is an idea: We prove the following identity instead.

$$ \int_{0}^{\frac{\pi}{2}} \arctan\left(\frac{2a\sin x}{1-a^{2}} \right) \, dx = 2 \sum_{n=0}^{\infty} \frac{a^{2n+1}}{(2n+1)^{2}}. $$

Expanding left-hand side,

\begin{align*} \int_{0}^{\frac{\pi}{2}} \arctan\left(\frac{2a\sin x}{1-a^{2}} \right) \, dx &= \sum_{n=0}^{\infty} \frac{(-1)^{n}}{2n+1} \int_{0}^{\frac{\pi}{2}} \left(\frac{2a\sin x}{1-a^{2}} \right)^{2n+1} \, dx \\ &= \sum_{n=0}^{\infty} \frac{(-1)^{n}}{2n+1} (2a)^{2n+1} \int_{0}^{\frac{\pi}{2}} \frac{\sin^{2n+1}x}{(1-a^{2})^{2n+1}} \, dx \\ &= \sum_{n=0}^{\infty} \sum_{j=0}^{\infty} \left( \frac{(-1)^{n}2^{2n+1} }{2n+1} \binom{2n+j}{j} \int_{0}^{\frac{\pi}{2}} \sin^{2n+1}x \, dx\right) a^{2j+2n+1}. \end{align*}

Plugging $m = n+j$, it follows that

\begin{align*} \int_{0}^{\frac{\pi}{2}} \arctan\left(\frac{2a\sin x}{1-a^{2}} \right) \, dx &= \sum_{m=0}^{\infty} \left( \sum_{n=0}^{m} \frac{(-1)^{n}2^{2n+1} }{2n+1} \binom{m+n}{m-n} \int_{0}^{\frac{\pi}{2}} \sin^{2n+1}x \, dx\right) a^{2m+1}. \end{align*}

Thus plugging the Wallis formula, the problem reduces to showing that

$$ \sum_{n=0}^{m} (-1)^{n} \frac{(m+n)!}{(m-n)!} \left( \frac{n!2^{2n}}{(2n+1)!} \right)^{2} = \frac{1}{(2m+1)^{2}}. $$

But I have no idea how to prove this.

$\endgroup$
6
  • $\begingroup$ As a side note, if the first line is true, then for $ |a| \le 1$, $$ \int_{0}^{\pi /2} \arctan\left(\frac{2a\sin x}{1-a^{2}} \right) \, dx = 2 \int_{0}^{\pi /2} \arcsin( a \sin x) \ dx$$ $\endgroup$ – Random Variable Nov 28 '13 at 21:59
  • $\begingroup$ @RandomVariable, that identity fails. The left-hand side is $2\chi_{2}(a)$, while the right-hand side is $4\chi_{2}\left(\frac{\sqrt{a^{2}+1}-1}{a}\right)$. $\endgroup$ – Sangchul Lee Nov 29 '13 at 6:12
  • $\begingroup$ I'm fairly certain that the right-hand side is also $2 \chi_{2} (a)$. Notice that the integrand is $\arcsin (a \sin x)$ and not $\arctan (a \sin x)$. $\endgroup$ – Random Variable Nov 29 '13 at 6:28
  • $\begingroup$ @RandomVariable Oh, I just misread the right-hand side. Thank you! Recently it's getting slightly harder to read on screen. $\endgroup$ – Sangchul Lee Nov 29 '13 at 6:30
  • $\begingroup$ Integrating the identity $\tan^{-1}\left(\frac{2a\sin x}{1-a^2}\right)=\tan^{-1}(aie^{-ix})\tan^{-1}(aie^{ix})$ over $x$ from $0$ to $\pi/2$ will fetch your identity immediately. $\endgroup$ – Antonio DJC Oct 20 '17 at 5:46
3
$\begingroup$

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ \begin{align}&\color{#c00000}{\int_{0}^{\pi/2}\arctan\pars{a\sin\pars{x}}\,\dd x} ={\pi \over 2}\,\arctan\pars{a} -\int_{0}^{\pi/2}x\,{a\cos\pars{x} \over a^{2}\sin^{2}\pars{x} + 1}\,\dd x \\[3mm]&={\pi \over 2}\,\arctan\pars{a} -a\,\Re\color{#00f}{\int_{0}^{\pi/2}{x\cos\pars{x} \over 1 + \verts{a}\sin\pars{x}\ic}\,\dd x} \end{align}

\begin{align}&\color{#00f}{\int_{0}^{\pi/2}{x\cos\pars{x}\over 1 + \verts{a}\sin\pars{x}\ic}\,\dd x} = \oint_{\verts{z}\ =\ 1 \atop {\vphantom{\Huge A}0\ <\ {\rm Arg}\pars{z}\ <\ \pi/2}} {-\ic\ln\pars{z}\pars{z^{2} + 1}/\pars{2z}\over 1 + \verts{a}\pars{z^{2} - 1}/\pars{2\ic z}}\,{\dd z \over \ic z} \\[3mm]&=\ic \oint_{\verts{z}\ =\ 1 \atop {\vphantom{\Huge A}0\ <\ {\rm Arg}\pars{z}\ <\ \pi/2}} {\ln\pars{z}\pars{z^{2} + 1} \over \verts{a}z^{2} + 2\ic z - \verts{a}} \,{\dd z \over z} \\[3mm]&={\ic \over \verts{a}} \oint_{\verts{z}\ =\ 1 \atop {\vphantom{\Huge A}0\ <\ {\rm Arg}\pars{z}\ <\ \pi/2}} {\ln\pars{z}\pars{z^{2} + 1} \over \pars{z - z_{-}}\pars{z - z_{+}}} \,{\dd z \over z}\,,\qquad z_{\pm} \equiv {-\ic \pm \root{a^{2} - 1} \over \verts{a}} \end{align}

Note that $\ds{z_{-}\,z_{+} = -1}$.

Also, \begin{align}&{z^{2} + 1 \over \pars{z - z_{-}}\pars{z - z_{+}}} =\pars{{z^{2} + 1 \over z - z_{+}} - {z^{2} + 1 \over z - z_{-}}} \,{1 \over z_{+} - z_{-}} \\[3mm]&={1 \over z_{+} - z_{-}}\,\pars{z + z_{+} + {z_{+}^{2} + 1 \over z - z_{+}} -z - z_{-} - {z_{-}^{2} + 1 \over z - z_{-}}} =1 + {1 \over z_{+} - z_{-}} \sum_{\sigma = \pm}\sigma\,{z_{\sigma}^{2} + 1 \over z - z_{\sigma}} \end{align}

and \begin{align}&{z^{2} + 1 \over \pars{z - z_{-}}\pars{z - z_{+}}z} ={1 \over z} + {1 \over z_{+} - z_{-}} \sum_{\sigma = \pm}\sigma\,{z_{\sigma}^{2} + 1 \over \pars{z - z_{\sigma}}z} \\[3mm]&={1 \over z} + {1 \over z_{+} - z_{-}} \sum_{\sigma = \pm}\sigma\,\pars{z_{\sigma}^{2} + 1} \pars{{1 \over z - z_{\sigma}} - {1 \over z}}\,{1 \over z_{\sigma}} \\[3mm]&=\pars{1 - {1 \over z_{+} - z_{-}}% \sum_{\sigma = \pm}\sigma\,\pars{z_{\sigma} - z_{-\sigma}}}\,{1 \over z} +{1 \over z_{+} - z_{-}}\sum_{\sigma = \pm} {\sigma\pars{z_{\sigma} - z_{-\sigma}} \over z - z_{\sigma}} \\[3mm]&=-\,{1 \over z} +\sum_{\sigma = \pm}{1 \over z - z_{\sigma}} \end{align}

\begin{align}&\color{#00f}{\int_{0}^{\pi/2}{x\cos\pars{x}\over 1 + \verts{a}\sin\pars{x}\ic}\,\dd x} \\[3mm]&=-\,{\ic \over \verts{a}}\ \underbrace{% \oint_{\verts{z}\ =\ 1 \atop {\vphantom{\Huge A}0\ <\ {\rm Arg}\pars{z}\ <\ \pi/2}} {\ln\pars{z} \over z}\,\dd z}_{\ds{=\ -\,{\pi^{2} \over 8}}}\ +\ {\ic \over \verts{a}}\sum_{\sigma=\pm} \oint_{\verts{z}\ =\ 1 \atop {\vphantom{\Huge A}0\ <\ {\rm Arg}\pars{z}\ <\ \pi/2}} {\ln\pars{z} \over z - z_{\sigma}}\,\dd z \end{align}

\begin{align}&\color{#c00000}{\int_{0}^{\pi/2}\arctan\pars{a\sin\pars{x}}\,\dd x} ={\pi \over 2}\,\arctan\pars{a} +\sgn\pars{a}\,\Im\sum_{\sigma=\pm} \oint_{\verts{z}\ =\ 1 \atop {\vphantom{\Huge A}0\ <\ {\rm Arg}\pars{z}\ <\ \pi/2}} {\ln\pars{z} \over z - z_{\sigma}}\,\dd z \end{align} With \begin{align}& \oint_{\verts{z}\ =\ 1 \atop {\vphantom{\Huge A}0\ <\ {\rm Arg}\pars{z}\ <\ \pi/2}} {\ln\pars{z} \over z - z_{\sigma}}\,\dd z =-\int_{1}^{0}{\ln\pars{y} + \ic\pi/2 \over \ic y - z_{\sigma}}\,\ic\dd y -\int_{0}^{1}{\ln\pars{x} \over x - z_{\sigma}}\,\dd x \\[3mm]&=\ic\,{\pi \over 2}\int_{0}^{1}{\dd y \over y + z_{\sigma}\,\ic} +\int_{0}^{1}{\ln\pars{y} \over z_{\sigma}\ic + y}\,\dd y -\int_{0}^{1}{\ln\pars{x} \over -z_{\sigma} + x}\,\dd x \\[3mm]&=\ic\,{\pi \over 2}\,\ln\pars{1 + z_{\sigma}\ic \over z_{\sigma}\ic} +{\rm Li}_{2}\pars{-\,{1 \over z_{\sigma}\ic}} -{\rm Li}_{2}\pars{-\,{1 \over z_{\sigma}}} \\[3mm]&=\ic\,{\pi \over 2}\,\ln\pars{1 + z_{-\sigma}\ic} + {\rm Li}_{2}\pars{-z_{-\sigma}\ic} - {\rm Li}_{2}\pars{z_{-\sigma}} \end{align}

since \begin{align} &\int_{0}^{1}{\ln\pars{\xi}\,\dd\xi \over b + \xi} =-\int_{0}^{-1/b}{\ln\pars{-b\xi}\,\dd\xi \over 1 - \xi} =-\int_{0}^{-1/b}{\ln\pars{1 - \xi} \over \xi}\,\dd\xi \\[3mm]&= \int_{0}^{-1/b}{\rm Li}_{2}'\pars{\xi}\,\dd xi={\rm Li}_{2}\pars{-\,{1 \over b}} \end{align}

The final result becomes \begin{align} &\color{#c00000}{\int_{0}^{\pi/2}\arctan\pars{a\sin\pars{x}}\,\dd x} \\[3mm]&={\pi \over 2}\,\arctan\pars{a} + {\pi\sgn\pars{a} \over 2}\,\ln\pars{2\,{\verts{a} + 1 \over \verts{a}}} \\[3mm]&+\sgn\pars{a}\Im\left\lbrack% {\rm Li}_{2}\pars{-1 - \ic\root{a^{2} - 1} \over \verts{a}} -{\rm Li}_{2}\pars{-\ic + \root{a^{2} - 1} \over \verts{a}}\right. \\[3mm]&\phantom{\sgn\pars{a}\Im\bracks{}}\left.+{\rm Li}_{2}\pars{-1 + \ic\root{a^{2} - 1} \over \verts{a}} -{\rm Li}_{2}\pars{-\ic - \root{a^{2} - 1} \over \verts{a}}\right\rbrack \end{align}

$\endgroup$
0
$\begingroup$

Sangchul Lee showed that the problem reduces to showing that $$\sum_{n=0}^{m} (-1)^{n} \, \frac{(m+n)!}{(m-n)!} \left( \frac{n!2^{2n}}{(2n+1)!} \right)^{2} = \frac{1}{(2m+1)^{2}}. \tag{1} $$

The following is a way to prove $(1)$ using properties of hypergeometric functions.


Using the duplication formula for the gamma function, along with the fact that $$\frac{1}{(m-n)!} = \frac{(-1)^{n}(-m)_{n}}{m!}, $$ we can express the left side of $(1)$ as the hypergeometric series $$_{3}F_{2} \left(1,-m,m+1;\frac{3}{2}, \frac{3}{2}; 1 \right). $$

Then using Euler's integral representation of the generalized hypergeometric function, we have $$_{3}F_{2} \left(1,-m,m+1;\frac{3}{2}, \frac{3}{2}; 1 \right) = \frac{1}{2} \int_{0}^{1} (1-t)^{-1/2} \, _2F_{1} \left(-m, m+1; \frac{3}{2} ; t \right) \mathrm dt, $$

where $$_2F_{1} \left(-m, m+1; \frac{3}{2} ; t \right) = \frac{\sin \left[(2m+1)\arcsin (\sqrt{t}) \right]}{(2m+1)\sqrt{t}}. $$

(See my answer here to a previous question.)

Therefore, $$ \begin{align} \sum_{n=0}^{m} (-1)^{n} \, \frac{(m+n)!}{(m-n)!} \left( \frac{n!2^{2n}}{(2n+1)!} \right)^{2} &= \frac{1}{2(2m+1)} \int_{0}^{1} (1-t)^{-1/2} \, \frac{\sin \left[(2m+1)\arcsin (\sqrt{t}) \right]}{\sqrt{t}} \, \mathrm dt \\ &= \frac{1}{(2m+1)^{2}} \int_{0}^{(2m+1)\pi /2} \sin (u) \, \mathrm du \\ &= \frac{1}{(2m+1)^{2}}. \end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.